Peningkatan Pembelajaran IPS Berbasis Kearifan Lokal melalui Wayang Kertas pada Materi Sejarah Kelas 5 MI Nurul Falah Depok - Fadil, Khaidir; Arakian, Rajab; Asmahasanah, Salati (Lembaga Yasin AlSys, 2025)
The limited number of studies on the implementation of Social Studies (IPS) instruction based on local wisdom serves as the background of this research, despite the significant potential of such an approach in strengthening cultural identity and enhancing students’ understanding at the primary education level. This study aims to analyze the effectiveness of using Wayang Kertas (Paper Puppets) as an instructional medium to improve students’ comprehension of historical content in Grade V at MI Nurul Falah Depok. The method employed is Classroom Action Research (CAR) with a collaborative reflective design over two cycles, involving 20 purposively selected students. Data were collected through observations of teacher and student activities, documentation of the learning process, and post-tests of student learning outcomes, which were analyzed using both quantitative descriptive and qualitative methods. The results indicate a significant improvement in learning mastery, from 11 students meeting the standard in Cycle I to all students achieving mastery in Cycle II. Teacher activity increased from 94% to 100%, while student activity rose from 89% to 100%. These findings support constructivist and contextual learning theories, emphasizing the importance of meaningful learning experiences rooted in students’ cultural backgrounds. The study concludes that Wayang Kertas is an effective medium for enhancing conceptual understanding of history and student engagement in Social Studies learning. Theoretically, this research contributes to the literature on integrating local wisdom into education, while practically, it offers recommendations for teachers to utilize culturally rooted media to create more active and meaningful learning environments. Furthermore, this study opens avenues for further exploration on the long-term impact of local wisdom-based learning on historical concept retention and character development in students.